SURGICAL INFECTIONS THE SURGERY OF INFECTIONS - Rocha, José Joaquim Ribeiro (Medicina (Ribeirao Preto), 2008)
Infections occurring during hospitalisation and post-surgical infections are related to a combination of various factors, which are discussed in the present text. Prophylactic and pathogenic aspects, as well as the possibilities to surgically treat already established infections are presented.